PERAN SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH DALAM DISEMIANSI KEBIJAKAN DAERAH DI KABUPATEN PANGANDARAN - Elin Nurlianti; Dini Yuliani; Ii Sujai (Yayasan Nusantara Hasana Berdikari, 2026)
Dissemination is an activity aimed at individuals and groups to raise their awareness of the importance of receiving, obtaining, and utilizing information. The Secretariat of the Pangandaran Regency Regional People’s Representative Council (DPRD), as a supporting element of the legislative institution, plays a strategic role in disseminating information on regional policies to the public. This study aims to examine the role of the DPRD Secretariat in the dissemination of regional policies and their implementation in Pangandaran Regency. The method used was descriptive qualitative research, employing data collection techniques such as observation, interviews, and documentation, as well as data analysis through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the role of the Pangandaran Regency DPRD Secretariat has been carried out across all dimensions, though not yet optimally. This is due to the lack of structured standard operating procedures (SOPs), insufficient human resources, the public’s limited understanding of legal policies, and unequal public access to available information channels. Despite facing various obstacles, the DPRD Secretariat continues to strive to improve policy dissemination. Therefore, thorough preparation is necessary, taking into account all indicators that may influence the success of regional policy dissemination.